Emerging fatal gout disease in Chinese goslings linked to acute kidney injury induced by novel goose astrovirus infection - Bi, Zhuangli; Lv, Xuan; Zhang, Zicheng; Cai, Linying; Zhang, Miao; Li, Wanxiao; Ding, Yingying; Liu, Huiwen; Yang, Kang; Zhu, Yingqi; Liu, Guangqing; Wang, Guijun (Frontiers in Cellular and Infection Microbiology, 2024)
A novel goose astrovirus (GAstV) has broken out across China in recent years, causing widespread damage to the poultry industry. In goslings infected with GAstV, the leading cause of death is visceral gout. However, our understanding of the mechanism of gout formation in GAstV infection is largely inadequate. The aim of this study was to examine the pathogenicity of a GAstV strain and explore the molecular mechanisms of visceral gout caused by viral infection in goslings. The virulent GAstV strain HR2105/1 was effectively isolated from the visceral tissue of goslings in gout-affected areas. The whole genome of the HR2105/1 strain was sequenced and analyzed. Subsequently, we established a gosling gout models with experimental GAstV infection. Finally, we conducted a study on the mechanism of GAstV induced acute kidney injury. Phylogenetic analysis of the complete genome sequence showed that it was closely related to the strain circulating in China since 2016, and it was grouped within the GAstV-1 cluster. The clinical signs were reproduced by experimental infection of healthy goslings with the isolated strain and were found to be similar to those reported in clinical cases. Moreover, the virus exhibits strong renal tropism. Infection with the GAstV strain HR2105/1 was found to cause acute kidney injury, as evidenced by increased levels of uric acid and creatinine as well as severe pathological damage. Mechanistic experiments with Masson and Picrosirius Red staining revealed fibrosis in renal tissues after GAstV infection. Furthermore, TUNEL staining revealed that GAstV infection triggered renal cell apoptosis. Additionally, RT-qPCR revealed that GAstV infection caused an excessive inflammatory response by upregulating the expression of IL-1β, IL-6, IL-10, TGF-β, and iNOS in renal tissues. Overall, our findings demonstrate that GAstV infection causes renal damage by inducing renal cell apoptosis, fibrosis, and excessive inflammatory response, which subsequently leads to hyperuricemia and lethal visceral gout formation. This is the first systematic study on the etiology of lethal gout in goslings caused by GAstV infection, and we believe that the findings can guide vaccine development and therapeutic targets for GAstV-associated renal diseases.